Sistem Informasi Data Klien Kantor Notaris & PPAT Muhammad Hanafi, S.H. - Muntohar, Arif (Universitas Hamzanwadi, 2020)
Information systems using computer technology in the era of globalization have experienced very rapid developments in almost all business fields. The data processing process becomes faster, the information generated is more accurate, and has an important role for the progress and development of a company or agency when carrying out its work activities so that it is more structured and time efficient. Notary Office and PPAT Muhammad Hanafi, S.H. is a company engaged in services. The information system running, until now, has not been computerized. Data recording is still written in books so it requires a lot of Manpower, the process of searching for data and printing reports takes a long time because it is storage cabinets, data is also vulnerable to damage and loss. The research objective is to design and develop this information system to be computerized in order to solve existing problems. The research method uses the Waterfall Model Development Life Cycle (SDLC), while the data collection uses interviews, observation and literature study. The system design in this study employs the decomposition function, DFD and ERD. The research findings are in the form of desktop applications implement Java and MySQL. The test results using black box testing successfully display the main menu of the application for further manage by office staff. The result is expected to be able to provide a convenience to office staff when processing client data and resolving existing problems